La invitación a la libertad en Kant: su significado como concepto crítico-regulativom y su aportación real en el sujeto activo - Herrero Olivera, Laura (Logos. Anales del Seminario de Metafísica, 2007)
Based on the conditions of Kantian Theory of Knowledge, this paper investigates the proper place of freedom, considered from the practical point of view in which maxims try to achieve happiness. In the same way, reason recognize the necessary respect for the moral law. Where must freedom be placed? In the elections in the world of sense or in the submit to that law? Assumption of the second propos- al implies to set up the origin of morality in the reason that recognize itself subordinate to moral legislation and it that way becomes an active role in the establishment of morality.
Keywords: Nature; Freedom; Autonomy; Moral legislation